Penerapan Lesson Study dalam Meningkatkan Kemampuan Mengajar Guru Bahasa Inggris pada Madrasah Tsanawiyah Negeri Model Sorong - Effendi M. (Journal of Islamic Education Policy, 2016)
This study aims to describe the improvement of teachers' teaching ability, student learning activities, and student learning outcomes in the subjects of English at MTs Negeri Model Sorong. Subjects of this study are English teachers and the eighth grade students of MTs Negeri Model Sorong in Academic Year 2015/2016. This research is a Lesson Study-based School Action Research using a qualitative approach. Data are collected through observation, documentation, and test. The findings are that the application of Lesson Study provides a positive impact on upgrading teachers' professional skills at MTs Negeri Model Sorong. This improvement has an important impact on student motivation and learning outcomes in the English subject.Keywords: Lesson study, teaching ability, learning activities, learning outcome, English